Positioning Manipulate Real Property Object On Tourist Attraction Utilize Augmented Reality - R Y Endra; D R Agustina; S C Hadi (Bandar Lampung University (UBL), 2017)
The purpose of this riset was made to simplify positioning of real property on tourist attractions. This research adapts the virtual objects are displayed when tracking the location of the tourist spot as a marker. Users can see the components of real property using markerless augmented reality method in the form of virtual objects, where markers used as tracker is a tourist attraction directly.